2011
DOI: 10.1186/1477-7525-9-104
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life of Iranian children with type 1 diabetes: reliability and validity of the Persian version of the PedsQL™ Generic Core Scales and Diabetes Module

Abstract: BackgroundThe aim of this study was to measure health related quality of life (HRQOL) in Iranian children with type 1 diabetes and to test the psychometric properties of the Persian version of the PedsQL™ 4.0 Generic Core Scales and the PedsQL™ 3.0 Diabetes Module.MethodsParticipants were 94 children and adolescents diagnosed with type 1 diabetes for at least 3 months in Shiraz, southern Iran. Convergent, discriminant, and construct validity of the PedsQL™ 4.0 Generic Core Scales and the PedsQL™ 3.0 Diabetes M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
41
0
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 14 publications
9
41
0
13
Order By: Relevance
“…In the current study, negative statistically significant correlations were found between HRQOL domains with demographic and clinical characteristics (age, disease duration, BMI, SBP, and DBP), and positive statistically significant correlations with socioeconomic status (especially maternal education, p = 0.019) and age of onset of diabetes (for all PedsQL™ 4.0 Generic Core Scale and only for the treatment adherence of the PedsQL™ 3.0 Diabetic module) were illuminated in the studied diabetic patients. As regards the effect of disease duration on HRQOL, current results were in accord with the studies of Jafari et al 2011, Hilliard et al 2013, Abdul-Rasoul et al 2013 Costa and Vieira 2015. The negative impact of long diabetes duration on quality of life might result from significant deterioration in glycemic control, deterioration in treatment adherence over this time, and occurrence of long-term diabetes complications that reduce person's perception of well-being and productivity.…”
Section: Discussionsupporting
confidence: 89%
“…In the current study, negative statistically significant correlations were found between HRQOL domains with demographic and clinical characteristics (age, disease duration, BMI, SBP, and DBP), and positive statistically significant correlations with socioeconomic status (especially maternal education, p = 0.019) and age of onset of diabetes (for all PedsQL™ 4.0 Generic Core Scale and only for the treatment adherence of the PedsQL™ 3.0 Diabetic module) were illuminated in the studied diabetic patients. As regards the effect of disease duration on HRQOL, current results were in accord with the studies of Jafari et al 2011, Hilliard et al 2013, Abdul-Rasoul et al 2013 Costa and Vieira 2015. The negative impact of long diabetes duration on quality of life might result from significant deterioration in glycemic control, deterioration in treatment adherence over this time, and occurrence of long-term diabetes complications that reduce person's perception of well-being and productivity.…”
Section: Discussionsupporting
confidence: 89%
“…Just as in the case with the PedsQL™ 4.0 on Iranian children with chronic conditions [16,17], this study showed that the Persian version of the KIDSCREEN-27 has a good internal consistency, and excellent convergent and discriminant validity. However, although the PCM showed that all the items contributed adequately to their own domain, Rasch analysis revealed that the number of response categories should be reduced from five to four in the Persian version of the KIDSCREEN-27.…”
Section: Discussionsupporting
confidence: 62%
“…All the students in the chosen classes were automatically taken as samples of the study in the second stage. The Persian version of the PedsQL TM 4.0, translated and validated previously in Iran [23,24], generated a survey that was filled in by the school children and their mothers and fathers. A trained researcher explained the objective of the survey to children in each classroom and distributed the informed consent forms and questionnaires among the students to take home for their mothers and fathers.…”
Section: Participants and Instrumentmentioning
confidence: 99%